2016
DOI: 10.1007/s13197-016-2333-6
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of HMW glutenin subunits from Aegilops kotschyi to wheat through radiation hybridization

Abstract: High molecular weight glutenin subunits (HMWGS) are responsible for dough elasticity and bread making quality of bread wheat. Related wild non-progenitor species, Aegilops kotschyi possesses higher molecular weight x and y glutenin subunits than the bread wheat cultivars. A wheat-Aegilops substitution line with 1U chromosome was used for the transfer of (HMWGS) of 1U to wheat by using pollen radiation hybridization approach. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis profiling showed different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Yet this is the only success story using irradiation for introgression of Aegilops chromatin for wheat breeding until recently. Singh et al (2016) and Verma et al (2016) recently reported the production of a translocation by irradiation of Ae. kotschyi hybrids.…”
Section: The Use Of Other Aegilops Species and Chromosome Pairingmentioning
confidence: 99%
“…Yet this is the only success story using irradiation for introgression of Aegilops chromatin for wheat breeding until recently. Singh et al (2016) and Verma et al (2016) recently reported the production of a translocation by irradiation of Ae. kotschyi hybrids.…”
Section: The Use Of Other Aegilops Species and Chromosome Pairingmentioning
confidence: 99%
“…For example, TraesCS1D02G317300 , encoding the high molecular weight glutenin subunit, was specifically expressed in grain 14 dpa. The content of HMW‐GS in wheat grains is low, accounting for only about 10% of the traditional storage protein but may explain about 60% of the variation in bread baking quality of wheat (He et al., 2005; Singh et al., 2016). TraesCS2A02G035700 and TraesCS2D02G034900 , encoding the arginase family, were specifically expressed in cereals.…”
Section: Discussionmentioning
confidence: 99%
“…biuncialis increased the protein content, Zeleny sedimentation, grain hardness, and wet gluten content [ 51 ]; and Glu-1U k from Ae. kotschyi increased SDS sedimentation in wheat [ 52 ]. Furthermore, Dasypyrum villosum HMW-GS Glu-1V can improve protein content, Zeleny sedimentation, wet gluten content, and rheological properties of small fragment translocation line NAU425, which shows potential in wheat quality improvement [ 53 ].…”
Section: Discussionmentioning
confidence: 99%